2005
DOI: 10.1002/crat.200410359
|View full text |Cite
|
Sign up to set email alerts
|

Bridgman‐Stockbarger growth and X‐ray photoelectron spectroscopy study of LiY1‐xEuxF4 crystals

Abstract: Key words europium-doped lithium yttrium fluoride, Bridgman-Stockbarger growth, X-ray photoelectron spectroscopy, valence instability of europium. PACS 71.20. Ps, 73.20.At, 75.20.Ck, 81.10.Fq, 82.30.Lp LiY 1-x Eu x F 4 (x = 0; 0.1 nominally) crystals were obtained by a modified Bridgman-Stockbarger technique. Europium was found to coexist in the LiYF 4 :Eu crystal in two valence states, Eu 3+ and Eu 2+, the content of the latter being enhanced in the near-to-surface region. The presence of bulk divalent eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…According to references the two peaks at 1134.7 and 1124.4 eV in the XPS spectrum can be attributed to Eu 3+ and Eu 2+ 3d5/2 core levels, respectively [48,51,52] [48]. The XPS analysis suggests that the particle surface is significantly enriched in europium and it is present in both the Eu 2+ and Eu 3+ oxidation states.…”
Section: Physico-chemical Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to references the two peaks at 1134.7 and 1124.4 eV in the XPS spectrum can be attributed to Eu 3+ and Eu 2+ 3d5/2 core levels, respectively [48,51,52] [48]. The XPS analysis suggests that the particle surface is significantly enriched in europium and it is present in both the Eu 2+ and Eu 3+ oxidation states.…”
Section: Physico-chemical Characterizationmentioning
confidence: 99%
“…Binding energy values were calibrated against the hydrocarbon C 1s line (eV), present because of contamination from ambient air or transport conditions [46][47][48]. Photoluminescence excitation and photoluminescence spectra were acquired using a FluoroMax-4P TCSPC spectrofluorometer produced by Horiba (Horiba Scientific, Kyoto, Japan), containing Czerny-Turner monochromators for excitation and emission.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the lattice constants will not change significantly by a slight oxidation of YF 3 the XRD spectra were misinterpreted by assigning the additional peaks (arrow in Fig. 3a) to YF 3 and therefore concluding erroneously that the white parts were due to incongruent melting [5,6]. There is nearly no axial segregation for the micro-pulling-down growth, in opposite to Bridgman or Czochralski growth, where one gets, because of an effective segregation coefficient k < 1, a first part of the crystal full of white precipitates followed by a clear part of the crystal.…”
Section: Resultsmentioning
confidence: 98%
“…Abell et al [2] reported congruent melting when using high purity starting material and purified Argon atmosphere while Thoma et al [3] showed in their phase diagram incongruent melting with peritectic point at 52 mol% LiF/48 mol% YF 3 . The Czochralski [4], Bridgman [5] and micro-pulling-down technique [6] have been used to grow LiYF 4 using an off-stoichiometric composition. However, except for the reported Czochralski growth [4], where the atmosphere was purified, the crystals contained some opaque part full of inclusions which have been assigned to YF 3 .…”
Section: Introductionmentioning
confidence: 99%